A Comprehensive Review of Corn Protein‐derived Bioactive Peptides: Production, Characterization, Bioactivities, and Transport Pathways. Issue 1 (22nd November 2018) - Zhu, Biyang; He, Hui; Hou, Tao
Abstract: Bioactive peptides are specific peptide fragments that positively exert various functional and biological activities and ultimately influence health. Corn protein are potential precursor proteins for bioactive peptides. This review encompasses the studies reported to date on the production, isolation, purification, and characterization technologies of bioactive corn peptides (CPs), with particular attention being devoted to these peptides' different health effects, including antioxidant, antihypertensive, hepatoprotective, alcohol‐metabolism‐facilitating, anti‐inflammatory, anticancer, antimicrobial, and dipeptidyl peptidase IV (DPP‐IV) inhibitory activities. The review also describes studies examining the potential mechanisms believed to be involved in these bioactivities, and the possible absorption and transport pathways of CPs are summarized.